Titin-Truncating variants predispose to dilated cardiomyopathy in populations genetically similar to african and european reference populations. - John DePaolo; Marc R Bornstein; Renae Judy; Sarah Abramowitz; Shefali S Verma; Michael G Levin; Penn Medicine Biobank; Zoltan Arany; Scott M Damrauer (PLoS Genetics)
The effect of high percentage spliced in (hiPSI) TTN truncating variants (TTNtvs) on risk of dilated cardiomyopathy (DCM) has historically been studied among population subgroups defined by genetic similarity to European reference populations. This has raised questions about the effect of TTNtvs in diverse populations, especially among individuals genetically similar to African reference populations. To determine the effect of TTNtvs on cardiovascular disease risk, we leveraged whole exome sequencing and electronic health record data from 43,731 Penn Medicine Biobank (PMBB) participants recruited from across the Penn Medicine healthcare system. Fraction of genetic similarity to the 1000 Genomes Project (1000G) African (AFR) reference population was determined using ADMIXTURE analysis. Logistic regression was performed to evaluate the association of hiPSI TTNtvs with prevalent DCM and atrial fibrillation (Afib), and linear regression was used to evaluate the association with reduced left ventricular ejection fraction (LVEF) either using dichotomized genetically similar population subgroup analysis or integrating ADMIXTURE population fraction. When individuals were assigned to population subgroups based on genetic similarity to the 1000G reference populations, hiPSI TTNtvs conferred significant risk of DCM among those genetically similar to the 1000G European (EUR) reference population (OR=6.12, 95% confidence intervals [CI] 4.33 to 8.65, P < 0.001) and individuals genetically similar to the AFR reference population (OR=3.44, 95% CI 1.97 to 5.99, P < 0.001). These results were consistent when considering the effect of change in fraction of similarity to the African reference population by ADMIXTURE as a continuous variable. Similar results were observed for the effect of TTNtvs on Afib and LVEF. Our findings demonstrate that TTNtvs are associated with increased risk of DCM, reduced LVEF, and Afib among a diverse cohort. There is no significant difference in effect of TTNtvs across fractions of similarity to the AFR reference population suggesting genetic background should not be considered when screening individuals for titin-related cardiovascular disease.